Polypharmacy in Elderly Patients: Clinical Risks, Drug Interactions and Strategies for Optimization – A Narrative Review - Wilczyński, Rafał; Wiązania, Kamil; Wróbel, Szymon; Kasperczak, Filip; Wrona, Weronika; Dorożalska, Małgorzata; Owsik, Julia; Wdowiak, Wiktoria; Ludwisiak, Hanna; Porażko, Maja (Quality in Sport, 2026)
Background. Population aging and the growing prevalence of multimorbidity have led to an increasing number of older adults receiving multiple medications. Polypharmacy, commonly defined as the use of five or more medications, is associated with adverse drug reactions, drug interactions, functional decline, hospitalization, and mortality. Age-related physiological changes further increase susceptibility to medication-related harm. Aim. To review the epidemiology, clinical risks, drug interactions, and optimization strategies associated with polypharmacy in elderly patients. Material and methods. A narrative review of the literature was conducted using peer-reviewed articles, clinical guidelines, and consensus documents addressing polypharmacy in adults aged 65 years and older. Evidence related to epidemiology, pharmacological changes associated with aging, adverse drug events, assessment tools, potentially inappropriate medications, and optimization strategies was analyzed and synthesized narratively. Results. Polypharmacy is highly prevalent among older adults, especially those with multimorbidity and frailty. Age-related pharmacokinetic and pharmacodynamic changes increase the risk of adverse drug reactions and clinically significant drug interactions. Common consequences include falls, delirium, cognitive impairment, hospitalization, and increased mortality. Tools such as the Beers Criteria, STOPP/START criteria, and Medication Appropriateness Index help identify inappropriate prescribing. Key optimization strategies include comprehensive geriatric assessment, medication review, deprescribing, and interdisciplinary care. Conclusions. Polypharmacy remains a major challenge in geriatric care. Regular medication review, individualized treatment planning, and deprescribing interventions are essential to reduce medication-related harm and improve clinical outcomes in older adults.